2020
DOI: 10.1109/access.2020.2979477
|View full text |Cite
|
Sign up to set email alerts
|

Risk Assessment Scheme for Mobile Applications Based on Tree Boosting

Abstract: In the forthcoming era of IoT, where everything will be connected, mobile devices will play a key role in providing data sharing and user-centric services between devices. In such a service environment, if a mobile application is vulnerable to security threats and exposed to malicious behavior, malware can spread to hundreds of millions of connected devices. In particular, it is important to isolate and respond quickly to malicious mobile code. This requires the prediction of malicious behavior. Currently, sec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 19 publications
1
6
0
Order By: Relevance
“…We also evaluated the effectiveness of ACAMA with AVClass. In summary, the evaluation results show that ACAMA outperforms the previous approach proposed by Kim et al [11]. Also, we observed that ACAMA can classify 72.456% of malware that AVClass cannot classify.…”
Section: Discussionsupporting
confidence: 55%
See 4 more Smart Citations
“…We also evaluated the effectiveness of ACAMA with AVClass. In summary, the evaluation results show that ACAMA outperforms the previous approach proposed by Kim et al [11]. Also, we observed that ACAMA can classify 72.456% of malware that AVClass cannot classify.…”
Section: Discussionsupporting
confidence: 55%
“…Figure 9 shows the accuracy comparison results between ACAMA and a malicious application detection system proposed by Kim et al [11], closely related with ACAMA, that use APIs as a feature. e verification accuracy is a result of malicious detection by reapplying the list to the training dataset after removing 10% of it to verify the effectiveness of the classifier.…”
Section: Malware Detection Resultmentioning
confidence: 99%
See 3 more Smart Citations